B-READY Indicators and Foreign Direct Investment: Evidence from Emerging and Advanced Economies - Rahmat Rahmat; Etty Soesilowati; Wahjoedi Wahjoedi (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The study examines the effect of the Business Entry, Taxation, and Utility Services indicators from the World Bank’s Business Ready (B-READY) framework on Foreign Direct Investment (FDI) inflows. Objective: The analysis aims to compare how these regulatory indicators influence investment attractiveness in Emerging Market Economies (EMEs) and Advanced Economies (AEs). Methods: The study employs a quantitative approach using cross-sectional data from 32 countries included in the B-READY dataset. The estimation is conducted using the Weighted Least Squares (WLS) method to address heteroscedasticity in cross-country data. Results: The results show that Business Entry and Taxation have a positive and statistically significant effect on FDI inflows in the full sample and in Emerging Market Economies (EMEs). However, the findings indicate no significant effect of these variables in Advanced Economies (AEs). The Utility Services indicator does not show a statistically significant impact on FDI inflows in either group. These findings suggest that regulatory efficiency related to business establishment and taxation plays a more important role in attracting foreign investment in developing economies. Conclusion: Policymakers in emerging economies should prioritize regulatory reforms that simplify business registration procedures and improve the efficiency of tax administration to enhance investment attractiveness.